Faktor-Faktor Yang Mempengaruhi Masyarakat Untuk Memilih Terapi Bekam Di Rumah Sehat Islamic Nurse Kota Pekanbaru Tahun 2024 - Bayu Rizky Alni; Roni Saputra (LPPM Universitas Abdurrab, 2024)
Nowadays, complementary medicine is increasingly in demand by the public, including cupping therapy. There are various reasons, factors and considerations that cause a person to prefer cupping complementary treatment over other types of treatment. The purpose of this study was to determine the factors that influence people to choose cupping therapy at Rumah Sehat Islamic Nurse. This study uses a quantitative research approach with descriptive methods. The population in this study were all people who chose cupping therapy at the Islamic Nurse Healthy House. The number of samples in this study were 68 respondents using accidental sampling technique. Unvariate data analysis techniques with data collection techniques using questionnaires. The results obtained from this study based on the mean value show that there is an influence of religious factors that influence people in choosing cupping therapy with a mean value of 14.35; psychological factors with a mean value of 13.46; knowledge factors with a mean value of 13.01; social factors with a mean value of 12.91; economic factors with a mean value of 12.44; cultural factors with a mean value of 11.10; personality factors with a mean niali of 10.07.The factor with the highest mean value influencing people to choose cupping therapy is religious factors and the factor with the lowest mean value influencing people to choose cupping therapy is personality factors. Suggestion: so that people can know the factors that influence in choosing cupping therapy and can add insight into cupping therapy.